2018
DOI: 10.1017/age.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Advertising Content Matter? Impacts of Healthy Eating and Anti-Obesity Advertising on Willingness to Pay by Consumer Body Mass Index

Abstract: This study examines the impacts of two types of advertising content—healthy eating and anti-obesity advertising—on the demand for healthy and unhealthy food and beverage items. We show that differentiating consumers by weight is crucial in fully understanding the effects of advertising content on food and beverage demand. We find that among overweight individuals, anti-obesity advertisements are more effective than healthy eating advertisements at reducing the demand for unhealthy items and increasing the dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…They also seemed more efficient than other clusters because they did not prefer to stay in the market for more than 15 min since they already knew about the personal indicators that would affect their choices. It can be said that this category was more experienced about healthy diets because of their purchasing experiences including their knowledge from mass media [89]; thus, although they are a smart buyer, they rely on nutrition information and are willing to pay more for it.…”
Section: Experienced and Proficient Buyersmentioning
confidence: 99%
“…They also seemed more efficient than other clusters because they did not prefer to stay in the market for more than 15 min since they already knew about the personal indicators that would affect their choices. It can be said that this category was more experienced about healthy diets because of their purchasing experiences including their knowledge from mass media [89]; thus, although they are a smart buyer, they rely on nutrition information and are willing to pay more for it.…”
Section: Experienced and Proficient Buyersmentioning
confidence: 99%
“…In the health sector, various studies have been estimated WTP with different methods for health services. For instance, Wang et al (2015) done study on the Impacts of Healthy Eating and Anti-Obesity Advertising on Willingness-to-Pay by Consumer Body Mass Index [ 7 , 8 ]. X Yu et al (2014) estimated WTP for the “Green Food” in China [ 9 ] Dror found that using bidding game among 3024 households at the rural location in India, about two-third of sample agree to WTP for health insurance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated a distinction between consumers in terms of weight in the understanding of the effects of the advertising content on food and beverage demand. Among overweight people, anti-obesity advertising was more effective than an advertisement for reducing the demand for unhealthy food [56].…”
Section: Previous Studies Related To Advertising and Consumer Behaviormentioning
confidence: 95%
“…They found that children used some food from the advertisements that were recently broadcast than older advertisements [55]. Wang et al (2018) investigated the impact of healthy eating advertising on demand for healthy and unhealthy foods. The results indicated a distinction between consumers in terms of weight in the understanding of the effects of the advertising content on food and beverage demand.…”
Section: Previous Studies Related To Advertising and Consumer Behaviormentioning
confidence: 99%